PANDANGAN SUTAN SJAHRIR TERHADAP KEMERDEKAAN INDONESIA 1945 DALAM PAMFLET PERJUANGAN KITA - Santosa, Yusuf Budi Prasetya (Universitas Sultan Ageng Tirtayasa, 2024)
This research wants to examine how Sutan Sjahrir's views on Indonesian independence through the Perjuangan Kita pamphlet. At the same time, it states if the pamphlet Perjuangan Kita is still relevant to be analyzed today. This research uses the historiography method that is strengthened by supporting literacy. Sutan Sjahrir was one of the founding fathers, who in the early days of Indonesian independence had the opportunity to put his thoughts into a pamphlet, which was later named Perjuangan Kita. The pamphlet Perjuangan Kita, which was written at the same time as the events of November 1945, contained Sutan Sjahrir's criticisms and suggestions on Indonesia's independence, and how it should be managed. There were at least three main points put forward by Sutan Sjahrir in the Perjuangan Kita pamphlet. First, the independence gained was not a gift from Japan. Second, the management of independence should not be given to former Dutch and Japanese accomplices. And thirdly, Sutan Sjahrir's displeasure with fascism that gave birth to blind nationalism in the Indonesian people.